IMPROVING ISLAMIC RELIGIOUS EDUCATION LEARNING OUTCOMES THROUGH THE PROBLEM-BASED LEARNING MODEL IN SENIOR HIGH SCHOOL - Hilabi, Abdurrahman; Umi Sulistyani; Sulthon Najib; Mochamad Dzikri Sultan Bahar Syach (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2026)
The low achievement of students in the subject of Islamic Religious Education (PAI) indicates the urgency of pedagogical innovations that can simultaneously escalate engagement and academic performance. In relation to this, this study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model in optimizing the learning outcomes of Islamic Religious Education (PAI) for 11th-grade students at SMAS Nurul Hikmah Jonggol. This study applies the Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles, where each cycle includes the phases of planning, action implementation, observation, and reflection. The subjects of the study consisted of 36 students, with data collection instruments in the form of learning outcome tests and instructional activity observation instruments. Data analysis was conducted using a mixed-methods approach; quantitative data were descriptively processed to calculate the class average and the percentage of classical learning completeness, while qualitative data were explored to represent the degree of participation and engagement of students during the learning process. The research results confirm a significant improvement in learning outcomes following the implementation of the PBL model. This is reflected in the fluctuation of the average class score, which increased from 72 at the pre-cycle stage to 80 in Cycle I, and reached 92 in Cycle II. In line with this, the percentage of classical learning completeness also experienced a progressive increase from 66.6% to 86.1% in Cycle I, and up to 97.2% by the end of Cycle II. These findings demonstrate that the PBL model is effective in stimulating learning outcomes, active participation, critical thinking skills, and collaborative skills in PAI learning. Based on this empirical evidence, PBL can be positioned as an innovative and contextual alternative learning strategy to continuously improve the instructional quality of PAI at the secondary education level.